2011
DOI: 10.1162/jocn.2011.21621
|View full text |Cite
|
Sign up to set email alerts
|

Working Memory Encoding Delays Top–Down Attention to Visual Cortex

Abstract: Abstract■ The encoding of information from one event into working memory can delay high-level, central decision-making processes for subsequent events [e.g., Jolicoeur, P., & DellʼAcqua, R. The demonstration of short-term consolidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 77 publications
1
19
0
Order By: Relevance
“…Another study of the P3b recording indicated that it has increased variability during the AB, which is consistent with the aforementioned findings, and suggests that the amount of delay in T2 processing varies from one trial to the next . Interestingly, the finding of delayed processing in posterior areas during the AB was extended by Scalf, Dux, and Marois (2011), who employed time-resolved fMRI to find delayed activation of occipital areas for T2 displayed during the AB. The neural sources of the P3b have been localized to posterior brain structures including posteriorparietal areas and the TPJ (e.g., Polich, 2003;Johnson, 1993).…”
Section: Introductionmentioning
confidence: 95%
“…Another study of the P3b recording indicated that it has increased variability during the AB, which is consistent with the aforementioned findings, and suggests that the amount of delay in T2 processing varies from one trial to the next . Interestingly, the finding of delayed processing in posterior areas during the AB was extended by Scalf, Dux, and Marois (2011), who employed time-resolved fMRI to find delayed activation of occipital areas for T2 displayed during the AB. The neural sources of the P3b have been localized to posterior brain structures including posteriorparietal areas and the TPJ (e.g., Polich, 2003;Johnson, 1993).…”
Section: Introductionmentioning
confidence: 95%
“…This finding was in accordance with our assumption that the increased perceptual difficulty of T 1 processing recruits more attention to T 1 and benefits the processing of a subsequent T 2 presented at the same location. It also clearly demonstrates that the effect of the T 1 noise manipulation on T 2 processing employed an underlying mechanism different from those in most of the previous studies, which have examined the effect of T 1 difficulty on T 2 performance by manipulating the memory load (Akyürek et al, 2010;Jolicoeur & Dell'Acqua, 1998;Ouimet & Jolicoeur, 2007;Scalf et al, 2011;Taatgen et al, 2009;Zhang, Zhou, & Martens, 2011), mental rotation (Taatgen et al, 2009;Zhang et al, 2011), or response selection (Giesbrecht, Sy, & Elliott, 2007) associated with T 1 processing. In those studies, more resources were needed to process T 1 in working memory-according to the resource accounts, for example-leaving fewer resources for T 2 processing.…”
Section: Discussionmentioning
confidence: 79%
“…For example, an unreported T 2 is nonetheless processed at a relatively high level-for example, the semantic level-indicating that the bottleneck of identifying a second target during the AB is not located at the perceptual processing stage (Chua, Goh, & Hon, 2001;Luck, Vogel, & Shapiro, 1996;Maki, Frigen, & Paulson, 1997;Shapiro, Driver, Ward, & Sorensen, 1997). Increasing the difficulty of encoding T 1 into working memory by increasing memory load leads to more severe AB on T 2 , indicating that T 2 performance varies as a function of the resource requirement of T 1 processing (Akyürek, Hommel, & Jolicoeur, 2007;Akyürek, Leszczyński, & Schubö, 2010;Jolicoeur & Dell'Acqua, 1998;Ouimet & Jolicoeur, 2007;Scalf, Dux, & Marois, 2011). On the other hand, if the distractor directly following T 1 , which provides backward masking to T 1 and prolongs T 1 processing, is replaced by a brief blank, the report of T 2 shows no (Chun & Potter, 1995;Raymond et al, 1992;Seiffert & Di Lollo, 1997) or little Nieuwenstein, Van der Burg, Theeuwes, Wyble, & Potter, 2009) performance deficit.…”
Section: Abstract Attentional Blink Rsvp Spread Of Sparingmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, working memory and selective attention constitute two basic cognitive processes related with social cognition and influenced by some factors presented in the police quotidian functions, for example in decisions making based on top-down processes of visual environmental and social cues (Scalf, Dux, & Marois, 2011). Working memory involves the integration of recent information necessary to perform decisions and to accomplish long term memory storages (Baddeley, 2003).…”
Section: Introductionmentioning
confidence: 99%